50 Issues - A Dozen Years of Service to Higher Education - Altbach, Philip (International Higher Education, 2008)
This is the 50th issue of International Higher Education. Our first issue appeared in the spring of 1995, almost 13 years ago. Our commitment then, as now, is to provide thoughtful analysis of contemporary events in higher education worldwide and information on current developments, especially in countries that do not receive much attention. We have a special concern with the broad issues of globalization and internationalization. Because of our sponsorship by a Jesuit university, we have been interested in issues relating to Catholic and Jesuit education worldwide. Ours has been an effort at network building and information provision.